Performance management of veterinarians : a case study of veterinary services in the Eastern Cape - Mutero, Gabriel (Rhodes University, Faculty of Commerce, Rhodes Business School, 2013)
In recent years, challenging economic conditions have stressed organizations, some to breaking point. Rather than waiting for external improvements, such as market growth or technological advances, many organizations are looking internally for performance and productivity gains (Boxall and Purcell, 2003). Consequently, the concept of performance management is receiving increased attention as a route to improved results and organisational growth (Boxall and Purcell, 2003). Likewise, increasing public pressure on governments to improve service delivery and account for the public purse have also forced many governments worldwide to implement a performance management system in one form or another (Ohemeng, 2009; Cameron and Sewell, 2003; Williams, 2005; Sehested, 2008). The South African Public Service has undergone much transformation since 2000. The transformation has been motivated by the Government's realisation that, as with governments throughout the world, there is a need to modernise and professionalise all spheres of Government. The guiding principles for this transformation are contained in the White Paper on the Transformation of the Public Service (1995) and the Batho Pele White Paper (1997). This has informed the Public Service Act: Act 32 of 2000 of which stipulates that public service organisations should have a performance management system to promote a culture of performance management amongst all staff. The performance management system must ensure that the public service administers its affairs in an economical, effective, efficient and accountable manner. Whereas performance management systems have been in existence in some parts of the world since the early 1970s (Armstrong and Baron, 2005), in the Eastern Cape Provincial Government (ECPG) the Performance Management and Development System (PMDS) can be considered to still be in its infancy stage. It was introduced slightly over a decade ago, with the objective of managing performance in a consultative, supportive and non-discriminatory manner (ECPG, 2001). The PMDS also aims to provide clarity to all employees on their role in the achievement of departmental and provincial goals. This was anticipated to result in enhanced organisational efficiency and effectiveness, accountability for the use of resources and the achievement of results (ECPG, 2001). 4 A literature review contained in this research indicates that internationally and locally, implementing performance management systems is beset with challenges such as conflicting interests between different groups such as professionals wanting autonomy, organisational culture, poor implementation, lack of capacity and resources, lack of institutional and leadership support, changing workplace environments and many others. However it has also been shown that performance management systems are one way of ensuring that employees are focused, goals are met and organisation move forward toward meeting their mission. This research, which has been grounded within a post positivist paradigm, describes the impact of the PMDS on veterinarians in their professional conduct. Semi-structured interviews were conducted with ten veterinarians within the Department, culminating in a total of seven and a half hours of interviewing time. The findings of this study were that the PMDS was minimally effective in achieving organisational goals and mission because of several reasons such as inconsistency in application, perceived unfairness, a lack of ownership of the system amongst workers and management, a lack of involvement, a dichotomy between policy and actual practice, geographical remoteness of subordinates resulting in dilution of information and influence, lack of resources and finally, the type and validity of indicators used. A significant finding was that having a non-veterinarian as a supervisor, impacted negatively on professional conduct. This was perceived to affect planning and goal setting, review and feedback discussions, as well as career advancement. The research ends with recommendations for practice and further research such as exploring management of professionals in multidisciplinary organisations. This research paper is organised and presented in three sections; the first section is in the format of an academic paper, and in addition to a concise review of the literature, will detail the findings, their discussion and conclusion. The second section contains a more expanded literature review of performance management of professionals and the third and last section describes and justifies the design of the study and how it was conducted.
Keywords: Performance management; Veterinarians -- South Africa -- Rating of